Prognostic value of depressed cardiac index after STEMI: a phase-contrast magnetic resonance study. (26th April 2021) - Schwaiger, J; Reinstadler, SJ; Holzknecht, M; Tiller, C; Reindl, M; Lechner, I; Lamina, C; Mayr, A; Graziadei, I; Bauer, A; Metzler, B; Klug, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: An invasively measured Cardiac Index (CI) of ≤2.2 l/min/m² is one of the strongest prognostic indicators after ST-elevation myocardial infarction, however knowledge is mainly based on invasive evaluations performed in the pre-stent era. Velocity-encoded Phase Contrast Cardiac Magnetic Resonance (PC-CMR) allows non-invasive determination of CI. Methods: In this prospective study CMR was performed in 406 stable and contemporarily revascularized patients a median of 3 days after STEMI. Forward stroke volume was assessed at the level of the ascending aorta by PC-CMR. Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) were determined by cine CMR. Major adverse cardiac events (MACE) were defined as the composite of death, myocardial infarction or hospitalization for heart failure. Results: Median CI was 2.52 l/min/m², 27% of patients had ≤2.2 l/min/m². Median LVEF was 53%, median GLS was -12.2%. During a median follow-up of 13.6 (12.1;62.9) months, 38 patients (8.7%) experienced a MACE. A depressed CI was significantly associated with MACE after adjustment for GLS and LVEF (HR = 2.55 (95%CI 1.10—5.28); p = 0.01), markers of myocardial injury (HR = 2.18, 95%CI 1.10-4.30, p = 0.02) and clinical parameters (HR = 2.42, 95%CI 1.19-4.90, p = 0.01). Adding CI to a model including LVEF and GLS led to significant discrimination improvement (0.55 [95%CI 0.18 - 0.91]; p = 0.003). Conclusions: A CI of 2.2 l/min/m² or less as measured by PC-CMR was present in 27% of clinically stable patients after STEMI, which strongly and independently predicted medium-term MACE. The prognostic value of a depressed CI was superior and incremental to LVEF and GLS.